FAKTOR PERUBAHAN BERTANI PADI SAWAH DARI NON ORGANIK KE ORGANIK DI DESA BOU KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Yusriadi Yusriadi; Putu Arimbawa; Mardin Mardin (Universitas Halu Oleo, 2022)
Organic farming is a technology that leads to the environment without using chemical elements. However, until now non-organic farming is still mostly practiced by farmers in Indonesia. The purpose of this study was to determine the characteristics of lowland rice farmers who switched from non-organic to organic, and to determine the factors of change in lowland rice farming from non-organic to organic. This research was conducted from February to April in Bou Village, Lambandia District, East Kolaka Regency. This research is a type of qualitative research using the case study method. The results showed that the characteristics of paddy rice informants who switched to organic farming had a basic education level, and the average age was still productive, with more or less 3 years of farming experience and had relatively narrow cultivated land. Factors changing paddy rice farming from non-organic to organic are divided into two, namely internal factors (health factors, education factors, income level factors), and external factors (scarcity of organic rice, and the high cost of chemical fertilizers).